2010
DOI: 10.1007/s00234-010-0736-z
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a central vein within white matter lesions on susceptibility weighted imaging: a specific finding for multiple sclerosis?

Abstract: Our results indicate that the detection of a central vein within a WML should not be considered a specific finding for MS; it is also found in WMLs of other etiologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 22 publications
1
45
2
Order By: Relevance
“…Our study is one of only several that have demonstrated the feasibility of detection of CVS on 3T MRI in MS,19, 20, 30, 31 and only a few studies have investigated whether the CVS distinguishes MS from other populations at 3T 16, 18. Lummel et al 16.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our study is one of only several that have demonstrated the feasibility of detection of CVS on 3T MRI in MS,19, 20, 30, 31 and only a few studies have investigated whether the CVS distinguishes MS from other populations at 3T 16, 18. Lummel et al 16.…”
Section: Discussionmentioning
confidence: 90%
“…One such method may be detection of the “central vessel sign” (CVS) 10. It has been known from histopathological studies at autopsy that most MS lesions are centered around veins,11 and only recently have a variety of imaging techniques using susceptibility‐weighted imaging on ultrahigh‐field 7‐tesla (T) research magnets demonstrated this relationship in vivo 12, 13, 14, 15, 16, 17. A small number of studies have also evaluated the ability of 3T scanners, which are used routinely in clinical practice, to detect a “central vessel” (CV) in MS lesions 18, 19, 20, 21.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have utilized a 3D T2*-weighted GRE sequence to overcome the slice gap issue, and have applied parallel imaging to shorten scan time while maintaining high image resolution (typically 0.5 × 0.5 × 1-3 mm) 39,45,54,55 . These T2*-weighted images can be post-processed using the susceptibility-weighted imaging (SWI) technique to further enhance venous conspicuity 56 .…”
Section: Statements and Recommendationsmentioning
confidence: 99%
“…Collection of multiple echoes within a single TR acquisition does not prolong scan time compared to the time needed to acquire a single echo. 5 Further, SWAN can acquires thin slice 3D images and, as a result, is expected to reduce partial volume averaging. The SWAN approach may be especially useful in evaluating brain tissue likely exposed to large susceptibility diŠer-ences at air-to-soft tissue or bone-to-soft tissue interfaces of the skull base.…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe the paucity of literature means that the diagnostic ability of SWAN has not been determined in comparison with the latter two. 4,5 We aimed to investigate diagnostic ability among these 3 imaging techniques with regard to commonly desired aspects of susceptibility-weighted MR imaging-detection of mineralization and cerebral microbleeds, and depiction of small venous vasculature.…”
Section: Introductionmentioning
confidence: 99%